Adapting a propane turkey fryer to manipulate temperature in aquatic environments. Issue 10 (16th July 2021) - Konecny, Cassandra A.; Brownlee, Graham R. P.; Harley, Christopher D. G.
Abstract: There is a growing need to better understand the potential impacts of altered thermal regimes on biodiversity and ecosystem function as mean temperatures, and the likelihood of extreme temperatures, continue to increase. One valuable approach to identify mechanisms and pathways of thermally driven change at the community level is through the manipulation of temperature in the field. However, where methods exist, they are often costly or unable to produce ecologically relevant changes in temperature. Here, we present a low‐cost, easily assembled and readily customizable thermal manipulation system for tide pools or other small bodies of water—the Seaside Array for Understanding Thermal Effects (SAUTE)—and demonstrate its ability to effectively alter the temperature in tide pools. During our 3‐hr heating manipulation, heated pools reached temperatures 4℃ warmer than unmanipulated pools. During the cooling manipulation, cooled pools remained on average 1.8℃ cooler than control pools. The novel SAUTE system can be used to alter the temperature of tide pools in situ. Furthermore, it could be modified to heat other environments such as freshwater vernal pools and settlement tiles in a realistic and meaningful manner, serving as a useful tool to test questions surrounding the relationship between climate warming, thermal variability and ecological processes in natural aquatic communities.